Bipolar electrocaloric effect in Pb1−xGdx(Mg1+x/3Nb2–x/3)O3 ceramic: Relaxor with super-dipolar glass state. (15th March 2019) - Pandey, Adityanarayan H.; Awasthi, A.M.; Gupta, Surya Mohan
Abstract: The electrocaloric (EC) effect is calculated for Pb1− x Gd x (Mg1+ x /3 Nb2– x /3 )O3 ; x = 0 to 0.1 relaxors from temperature dependent heat capacity and polarization measurements, using a thermodynamic Maxwell equation. Polarization change with temperature reveals an anomalous behaviour around the glass transition temperature for x ≥ 0.05, which is in the vicinity of a crossover from positive to negative EC effect, which is explained evoking the critical slowing-down of the polar nano-domains dynamics to super-dipolar glass state upon cooling. The maximum negative EC coefficient ξmax is observed to decrease from 0.4 K-mm/kV at 164 K to 0.1 K-mm/kV with x . Graphical abstract: Unlabelled Image